Pazopanib radio-sensitization of human sarcoma tumors - Wang, Feng (Oncotarget, 2018)
Recent data in our laboratory indicate that engagement of host-derived microenvironmental elements impact tumor response to single high dose radiation therapy (SDRT). In these studies we showed that microvascular endothelial damage plays a critical role in tumor response as regulator of direct lethal damage of SDRT. Using a genetic model of Acid Sphingomyelinase (ASMase)-deficient mice we showed that activation of this enzyme by SDRT-induced damage in the endothelium is mandatory for tumor cure. ASMase activation triggers ceramide-mediated apoptosis, and therein microvascular dysfunction, which increased the vulnerability of tumor cells to lethal damage by radiation. Angiogenic factors repressed this activity while a monoclonal antibody targeting VEGF, de-repressed ASMase activity and radiosensitized tumor endothelium when delivered immediately prior to SDRT. In this study, we tested the effect of SDRT in combination with the short-acting anti-angiogenic agent, Pazopanib (anti-VEGFR-1/2/3, PDGF-α/β and c-kit), in two xenograft models of human sarcoma. Pre-treatment with a single dose of Pazopanib increased SDRT-induced ASMase activity and endothelial dysfunction in vitro and in vivo, enhancing SDRT tumor cure, and exhibiting critical dependence on timing relative to SDRT exposure, suggesting a mechanism of action identical to that demonstrated for anti-VEGF/VEGFR2 antibodies. These results demonstrate the ability of Pazopanib to shift the response towards tumor cure and could therefore have a significant impact on clinical trial development in combination with SDRT for sarcoma cancer patients.